DNA of Solenidium lunatum (Lindl.) Kraenzl (Orchidaceae) - Cardoso, Elisa dos Santos; Lima, Joameson dos Santos; Farias, Cyntia Beatriz Magalhães; Dardengo, Juliana de Freitas Encinas; Rossi, Ana Aparecida Bandini (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
Molecular characterization and genetic diversity studies based on molecular markers require a quality DNA, free of contaminants such as phenols and polysaccharides, and also a sufficient quantity to perform polymerase chain reactions (PCR). Plant DNA extraction protocols are mostly based on the CTAB (Cetyltrimethylammonium Bromide) method, however due to the particularities of each plant, adjustments are required regarding the reagents used and the amount of them. The objective of this study was to evaluate different concentrations of CTAB and β-mercaptoethanol in the DNA extraction protocol of Solenidiumlunatum (Lindl.) Kraenzl (Orchidaceae), aiming future studies of genetic diversity using molecular markers. For the CTAB, 2% and 5% concentrations were tested, while for β-mercaptoethanol, 0% and 2% weretested. To verify if the extracted material was amenable to amplification, tests were performed with three primers ISSR (Inter Simple Sequence Repeats). The results indicated that all the methods were efficient in extracting DNA with quantity and quality required to perform PCRs. However, it is recommended to use the 2% CTAB protocol without addition of β-mercaptoethanol, since no significant differences in amplification results were found. The use of this protocol produces a quality material, capable of amplification, with reduction of costs and risk of intoxication.